2020
DOI: 10.1108/jeas-03-2020-0030
|View full text |Cite
|
Sign up to set email alerts
|

The inter-temporal relationship between workers' remittances and consumption expenditure in Sri Lanka

Abstract: PurposeThe objective of this study is to examine the inter-temporal relationship between workers' remittances and consumption expenditure in Sri Lanka over the period of 1975–2017 using the annual time series data.Design/methodology/approachTo test the order of integration of the variables used in this study, the augmented Dickey–Fuller (ADF) and Phillips and Perron (PP) unit root tests were employed. The autoregressive distributed lag (ARDL) bounds cointegration technique was used to examine the long-run rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…This study found that remittance positively and significantly contributes to the human development score with the expected sign and direction. This finding is consistent with the existing literature [ 19 , 28 , 34 ]. Workers’ international remittance positively affects human development in the long run.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This study found that remittance positively and significantly contributes to the human development score with the expected sign and direction. This finding is consistent with the existing literature [ 19 , 28 , 34 ]. Workers’ international remittance positively affects human development in the long run.…”
Section: Discussionsupporting
confidence: 94%
“…In Sri Lanka, remittance is a significant predictor of human capital formation. However, the development effect varies based on the government’s approach to migrants, which indicates that institutions and governmental policy are closely intertwined with remittance inflow [ 32 , 34 ]. A positive association exists between human development and remittance: the composite index combined with long healthy life, knowledge accessibility and a decent living standard [ 35 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The fourth is that the ARDL model simultaneously estimates both long-run and short-run dynamics by using a single reduced form of the equation (Harris and Sollis, 2003). The final advantage is that the ARDL Bounds cointegration technique accommodates the fractionally integrated variables in estimating the model (Aslam and Sivarajasingham, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…For the poor vulnerable households, remittances can prove very useful in times of economic shocks as both income and consumption smoothing strategies (Quartey, 2006). At the macro level, the inter-temporal relationships between remittances and consumption expenditure has been investigated (Aslam and Sivarajasingham, 2020). In rural areas and developing countries at large, the financial system is usually underdeveloped, limiting remittances received through the financial system.…”
Section: Literature Reviewmentioning
confidence: 99%